Hubungan Status Gizi Dan Menyusui Dengan Involusio Uteri Pada Ibu Post Partum - Vinny Alvionita; Tika Pasae; Herawaty Herawaty; Sumarni Syam; Ummul Khair; Inez Vravty Lestari (Jurnal Keperawatan Muhammadiyah, 2022)
Uterine Involution is normal shrinking of an organ after it fulfills its function, for example uterine shrinks after giving birth. Objective: To identify the correlation of Nutritional And Breastfeeding Status With Uteri Involution in Postpartum Women I. This research employed analytical survey with cross sectional study design. The population was all normal postpartum women in Sawerigading General Hospital of Palopo City numbering 50 people. Samples were taken using accidental sampling. Data consisted of primary data (collected through observation sheet) and secondary data (article search and data from Sawerigading General Hospital of Palopo City). The data were processed using Statistical Product And Service Solutions (SPSS) and analyzed using with chi-square test and presented in the frequency distribution table. There was a correlation between nutritional status and uterine involution in postpartum (p-value =,001 < α value = ,05) and there was a correlation between breastfeeding status and uterine involution in postpartum (p-value =,001 <α value = ,05). sThere are correlations of Nutrition and Breastfeeding Status with uterine involution in postpartum women.